2011
DOI: 10.1074/jbc.m111.297515
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal Kinase Regulates Soluble Aβ Oligomers and Cognitive Impairment in AD Mouse Model

Abstract: Background: Neuropathological mechanisms in Alzheimer disease (AD) are partially unknown. Results: Chronic JNK inhibition with a cell-permeable peptide (CPP) rescues memory deficits, LTP impairment, and reduces A␤ oligomers in a mouse model that mimics AD. Conclusion: JNK is crucial in AD neurodegenerative mechanisms. Significance: CPPs offer an important tool to interfere with neurodegeneration. JNK is a promising target against AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 45 publications
3
77
0
Order By: Relevance
“…29 We here explored the effect of D-JNKI1 treatment on long-term depression (LTD). LTD is an activity-dependent physiological phenomenon occurring in the dentate gyrus (DG) that also involves synaptic release of glutamate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 We here explored the effect of D-JNKI1 treatment on long-term depression (LTD). LTD is an activity-dependent physiological phenomenon occurring in the dentate gyrus (DG) that also involves synaptic release of glutamate.…”
Section: Resultsmentioning
confidence: 99%
“…27, 29 We used a ‘post-symptomatic' treatment as it is clinically more relevant. This treatment protocol was also supported by our results that demonstrate that JNK activation started at 2 months and persisted with a significant increase during AD progression.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] However, whether specific inhibition of central JNK activation would prevent the development of different pathological features remains to be fully investigated in vivo. [4][5][6][7][8][9][10][11] However, whether specific inhibition of central JNK activation would prevent the development of different pathological features remains to be fully investigated in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A growing body of evidence has shown that c-Jun N-terminal kinase (JNK), known as a stress-activated protein kinase, is involved in several pathophysiological processes of AD. [4][5][6][7][8][9][10][11] In addition, it has been proven that JNK activation mediates APP phosphorylation at threonine 668 site to facilitate Ab production in cultured cells, suggesting that active JNK is involved in Ab production. [4][5][6][7][8][9][10][11] In addition, it has been proven that JNK activation mediates APP phosphorylation at threonine 668 site to facilitate Ab production in cultured cells, suggesting that active JNK is involved in Ab production.…”
mentioning
confidence: 99%
“…58-60,[136][137][138][139][140][141] More recently, Ngoei et al identified the peptides L-PYC71N and D-PYC98 from a yeast twohybrid screen of a biodiverse gene fragment library 142,143. Both peptides are pan-JNK inhibitors…”
mentioning
confidence: 96%